Application of Scientific Approach through Problem Based Learning Model to Improve Critical Thinking Skills and Assessment Skills in Class 3A Third Semester Students at Patompo University - Hajar, Sitti; Fadjriani, Fadjriani; Puang, Datu; Rahman, Nawir (Universitas Negeri Makassar, 2024)
Soft skills in the form of critical thinking skills and argumentation skills are needed in solving problems, making decisions, and drawing conclusions, especially in dealing with global issues regarding the threat of depletion and degradation of natural resources. The low critical thinking skills and argumentation skills of third-semester students in class 3A at Patompo University Makassar prompted researchers to research to describe the application of a scientific approach through the Problem-Based Learning model. The results of the study show that applying a scientific approach through the Problem Basic Learning model can improve critical thinking skills in cycle II with an achievement of 75% being Critical. Furthermore, argumentation skills in cycle II at the claim stage are 1.56%, and the evidence stage is 2.32%. All stages of argumentation are high. The findings in this study indicate that teacher creativity is needed to help improve students' critical thinking skills and argumentation skills.